1999
DOI: 10.1074/jbc.274.9.5895
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Lysine Acetylation Specificity of Gcn5 in Native Complexes

Abstract: The coactivator/adaptor protein Gcn5 is a conserved histone acetyltransferase, which functions as the catalytic subunit in multiple yeast transcriptional regulatory complexes. The ability of Gcn5 to acetylate nucleosomal histones is significantly reduced relative to its activity on free histones, where it predominantly modifies histone H3 at lysine 14. However, the association of Gcn5 in multisubunit complexes potentiates its nucleosomal histone acetyltransferase activity. Here, we show that the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
271
1
11

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 348 publications
(299 citation statements)
references
References 47 publications
16
271
1
11
Order By: Relevance
“…Gcn5 acetylates histones H3 and H2B (Grant et al, 1997(Grant et al, , 1999. H3 acetylation is decreased approximately twofold in undifferentiated Gcn5 Ϫ/Ϫ cells (data not shown), indicating that Gcn5 is a major H3 HAT activity in these cells, but it is not the only one.…”
Section: Decreased Acetylation In Gcn5 Null Es Cells During Differentmentioning
confidence: 90%
“…Gcn5 acetylates histones H3 and H2B (Grant et al, 1997(Grant et al, , 1999. H3 acetylation is decreased approximately twofold in undifferentiated Gcn5 Ϫ/Ϫ cells (data not shown), indicating that Gcn5 is a major H3 HAT activity in these cells, but it is not the only one.…”
Section: Decreased Acetylation In Gcn5 Null Es Cells During Differentmentioning
confidence: 90%
“…In support of this view, Zac1 is here shown to increase the rate of acetylation of histone H4 versus H3 due to changes in PCAF's substrate affinities and catalytic activities. In this context, it is important to note that previous studies showed that association with other factors leads to a context-dependent acetylation pattern for the PCAF-related acetyltransferase Gcn5 (14). Among the factors that associate with Gcn5 are the adaptor proteins Ada2, which potentiates Gcn5 catalytic activity, and Ada3, which facilitates nucleosomal acetylation and an expanded lysine specificity (2).…”
Section: Discussionmentioning
confidence: 99%
“…HATs are almost exclusively found within larger multisubunit complexes with accessory proteins that modulate enzymatic activity and direct substrate specificity (2)(3)(4). For example, the yeast HATs Esa1 (KAT5) and Gcn5 (KAT2) alone are ineffective catalysts toward nucleosomal histones; both enzymes require association with other protein subunits for efficient acetyl transfer on nucleosomal substrates (5)(6)(7). Despite the prevalent reports of multisubunit HAT complexes, the molecular mechanisms by which accessory proteins regulate the acetyltransferases are largely unknown.…”
mentioning
confidence: 99%